Pengaruh Konten Gaming Pada Aplikasi Tiktok Terhadap Perilaku Generasi Z Diwilayah Sleman Yogyakarta - Afan Al fauzi; Afit Setyo Nugroho; Yanuardo Dwi Rangga (CV. ITTC INDONESIA, 2025)
This study examines the influence of gaming content on TikTok on the behavior of Generation Z. With the rapid growth of technology and social media, TikTok has emerged as a popular platform among teenagers, including Generation Z, who actively consume various content, including gaming-related media. Using a quantitative method with a survey approach, data were gathered from 100 active TikTok users aged 12-27 years in Sleman, Yogyakarta, through questionnaires. The data were analyzed using SPSS software to evaluate the relationship between the frequency of gaming content consumption and its impact on social behavior and daily interactions. The findings reveal a significant influence of gaming content on TikTok on Generation Z's behavior, accounting for 58% of the variance. Key effects include increased time spent on the platform, changes in entertainment preferences, and shifts in social interaction patterns. This research highlights how gaming content on TikTok shapes Generation Z's digital habits and underscores the importance of understanding social media's role in the social and psychological development of young people.